Enhancing the Nutrition and Dietary Patterns of Premature Infants by Optimizing Early Neonatal Nutrition - Xiao, Feng; Xian, Yuqi (Current topics in nutraceuticals research, 2024)
Preterm newborns with very low birth weight, defined as less than 1,500 g, often face challenges in meeting heightened nutritional demands due to physiological and metabolic stress and underdeveloped gastrointestinal systems. This study explored current guidelines and practices in nutritional management for very low birth weight infants, focusing on strategies, including providing human breast milk, donor human milk, parenteral nutrition, and combined nutrition. This retrospective cohort analysis, conducted in an institutional neonatal intensive care unit, reviewed data from medical records of preterm infants weighing 1,000–1,500 g admitted between March–November 2021. Nutritional management involved parenteral or combined nutrition. Data analysis included descriptive statistics, t-tests, Mann–Whitney tests, chi-square tests, and relative risk analysis. Of the 421 reviewed records, 106 met the inclusion criteria. A total of 31 infants received parenteral nutrition, while 75 received combined nutrition. Infants on combined nutrition demonstrated higher weight gain compared to infants on parenteral nutrition (P < 0.05). Relative risk analysis revealed varied associations between nutrition type and comorbidities, suggesting potential benefits and risks of each approach. Combined nutrition effectively met caloric and nutritional needs in very low birth weight infants without increasing morbidity and mortality. It positively impacted weight gain, indicating its viability as an alternative feeding approach.